1993
DOI: 10.1128/jcm.31.3.636-641.1993
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of specific immunoglobulin M antibodies to Plasmodium falciparum antigens in immunoprotection of humans living in a hyperendemic area, Burkina Faso

Abstract: Two seroepidemiological studies were performed in an area of Burkina Faso hyperendemic for malaria to estimate the protective role of immunoglobulin M (IgM) antibodies. Six cross-sectional surveys were carried out on children (ages, <16 years) in the village of Karankasso. The evolution of antibodies to crude extracts of Plasmodiumfalciparum (IgG or IgM antisomatic and IgG antiexoantigens) were tested by IFI or enzyme-linked immunosorbent assay and were followed up according to the fluctuations of the parasite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…The elevated levels of these antibodies in the Fulani as compared with the non-Fulani suggest a protective role for the IgG as shown earlier and a similar role for the IgM antibodies. These findings are in line with previous reports that have suggested a protective role for IgM antibodies against malaria infection [27,28] or disease severity [29]. The fact that surface IgM þ B lymphocytes with long-lasting memory can persist after the malaria transmission season [30] may explain such elevated levels of P. falciparum-specific IgM in the Fulani.…”
Section: Discussionsupporting
confidence: 92%
“…The elevated levels of these antibodies in the Fulani as compared with the non-Fulani suggest a protective role for the IgG as shown earlier and a similar role for the IgM antibodies. These findings are in line with previous reports that have suggested a protective role for IgM antibodies against malaria infection [27,28] or disease severity [29]. The fact that surface IgM þ B lymphocytes with long-lasting memory can persist after the malaria transmission season [30] may explain such elevated levels of P. falciparum-specific IgM in the Fulani.…”
Section: Discussionsupporting
confidence: 92%
“…1 It is highly antigenic and the gene encoding GLURP shows little polymorphism in geographically different P. falciparum isolates. 2,3 Moreover, previous immunoepidemiologic studies performed in high transmission areas have shown a high prevalence of antibodies against GLURP in adults, [4][5][6] as well as a significant association of high levels of GLURP-specific antibodies with low parasite densities 7,8 and protection against clinical malaria. 6,[9][10][11] In addition, there has been evidence that cytophilic antibody responses to GLURP play a primary role in protection against P. falciparum malaria by effector mechanisms such as antibody-dependent cellular inhibition (ADCI), 12 the cooperation of monocytes and antibodies impairing parasite multiplication.…”
Section: Introductionmentioning
confidence: 95%
“…Several studies have reported Pf-specific IgM responses in malaria-exposed populations and in some cases have shown that these responses associate with protection from clinical malaria (9)(10)(11)(12)(13)(14)(15). For example, the malaria-resistant Fulani in West Africa have a higher breadth and magnitude of Pfspecific IgM compared to the more susceptible Dogon, whereas Pf-specific IgG did not distinguish the two groups (16,17).…”
Section: Introductionmentioning
confidence: 99%